Assessment of river health using in situ water quality parameters and miniass protocol in the Marico and Crocodile rivers, North West Province, South Africa - Nsubuga, F.W.N. (Francis Wasswa Nkugwa) (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.